FLUID DYNAMICS PROCESSES AT THE CENTRAL SAKHALIN FAULT (BASED ON OBSERVATIONS OF THE YUZHNO-SAKHALINSK MUD VOLCANO) - Valery V. Ershov (Геодинамика и тектонофизика, 2015)
The Yuzhno-Sakhalinsk mud volcano is located in the southern part of the Sakhalin Island within the area of the Central Sakhalin fault, one of the largest disjunctive dislocations of the island. The volcano was monitored during field seasons in the period from 2005 to 2007, and data on flow rates, chemical and isotope compositions of gases, temperature and chemical composition of watermud mixture in the volcano’s blowouts were collected and analysed. During the observation period, seismic activity in the region under study was significantly variable in time and space. The monitoring results revealed «traces» of two earthquakes in the blowout activity of the Yuzhno-Sakhalinsk mud volcano – the Gornazavodsk earthquake, that took place on 17 (18) August 2006, and the Nevelsk earthquake of 2 August 2007. Based on results of our analyses of the field data and mathematical simulation data, it is possible to conclude that an additional inflow of «deep geofluids» could not have been a major trigger of the activity of the volcano after the earthquakes. In our opinion, all the observed anomalies may result from «water – rock – gas» interactions in the top part of the mud volcano’s feeder channel. A combination of water and gas flows in the volcano’s channel and silica-alumina rocks comprises a specific geochemical system that is sensitive to external (seismic) impacts. Therefore, comprehensive consideration of physical and chemical processes within fluid-dynamic systems is required for assurance of correct interpretation of empirical data.